Key competences : citizens' perspectives - Mannonen, Joonas (2019)
Over the past several decades, the competences that education systems produce have emerged as a pervasive topic in educational policy discourse. In addition to many national and international evaluations of and frameworks for essential future competences, there is a need to understand the perspectives of citizens. This study focuses on the competences that research participants from a diverse set of social backgrounds in Finland considered to be essential in the future. In all, 70 research participants were interviewed in 10 Finnish municipalities using a combination of convenience and purposive sampling. A holistic typology of competence (Le Deist & Winterton, 2005) was used as the basis for the content analysis. The results illustrate 33 key competences as described by the participants. Particularly, the participants emphasized the importance of meta competences and social competences necessary in the future world and working life. The reasoning behind why the participants felt meta competences to be important was examined. A high level of congruence with the aims of many recent national and international educational policies is discussed. This study introduces novel knowledge for adults’ competences and can be used as a starting point for future studies in developing better understanding of the competences that are needed in different industries.